Perkembangan Anak Usia Dini Dalam Pendekatan Holistik : LIterature Review - Lina Haryani; Leni Liana Sari (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2026)
Background: Child development involves various interconnected aspects, such as physical, cognitive, social-emotional, and language aspects, so a holistic approach is needed to understand development as a whole. Various studies have shown that imbalanced stimulation, especially when stimulation focuses only on academic abilities while social-emotional aspects are less considered, results in children not receiving optimal developmental support. This emphasizes the importance of a holistic approach in understanding child development. Objective: To review the literature related to various aspects of early childhood development and describe a holistic approach in supporting child development as a whole.Method: This study employed a literature review using a narrative review approach. Data were obtained from the Google Scholar and PubMed databases, covering publications from 2021 to 2025, using Boolean-based keywords. A total of 35 articles were initially identified (n=35), of which 9 articles met the inclusion criteria (n=9) and were included in the analysis. Data were analyzed descriptively by categorizing findings based on developmental domains. Results: Of the 35 identified articles, 9 met the inclusion criteria and were included in the analysis. The synthesis indicates that early childhood development is consistently described as a multidimensional process with interrelated domains. The reviewed studies highlight the interconnections among cognitive, language, motor, and socio-emotional development, with varying emphases on play-based activities, parenting practices, learning environments, and the use of educational media. In addition, several studies report that developmental stimulation practices remain predominantly academically oriented and do not fully reflect a holistic approach. Conclusion: A holistic approach is an important strategy for understanding and monitoring child development. Positive parenting, family environment, social interaction, and collaboration between parents, health workers, and educators play an important role in supporting child development in various aspects.